Exploring learning-oriented assessment in EAP writing classrooms: teacher and student perspectives - Maggie Ma (Language Testing in Asia, 2023)
Abstract Despite a growing interest in learning-oriented assessment in recent years, there is limited research on its implementation in language classrooms from both teacher and student perspectives, especially from an ecological lens. To address the research gap, this case study explored the implementation of learning-oriented assessment in three EAP writing classrooms, including both perceived success of and obstacles to implementation. Major data sources included interviews with teachers and students as well as classroom observation. The findings showed the different extents to which the teachers and students perceived and shaped/utilized the affordances of each dimension of learning-oriented assessment as well as the various ways in which their fields of affordances were aligned, due to micro-level, meso-level, and macro-level factors. Based on the findings, a model of learning-oriented assessment in EAP writing classrooms has been proposed and pedagogical implications have been discussed.